Rite Communication in The Nyadran Tradition in Sidoarjo - Abida Al Aliyah; Totok Wahyu Abadi; Ferry Adhi Dharma (Kanal: Jurnal Ilmu Komunikasi, 2020)
is a form of ritual that still exists among the coastal community which is full of elements of intercultural communication. This study aims to analyze communication in the ritual in and Villages, Sidoarjo Regency. This qualitative research uses the communication ethnographic approach presented by . Data collection was carried out with participant observation and in-depth ethnographic interviews with nine informants. The sampling technique uses sampling. After being collected, the data were analyzed by SPEAKING analysis from . The results showed that the rite is a communication made by the fishing community as a form of gratitude to Allah SWT who has provided an abundance of sustenance. Second, the offerings in the ceremony are symbols that have the meaning of a blessing in life and success at work. Third, is a form of local wisdom manifested in cooperation, giving, environmental preservation, and hospitality.